Reliability Assessment of Scores from Video-Recorded TGMD-3 Performances - Pauli Rintala; Arja Sääkslahti; Susanna Iivonen (Human Kinetics, 2022)
This study examined the intrarater and interrater reliability of the Test of Gross Motor Development—3rd Edition (TGMD-3). Participants were 60 Finnish children aged between 3 and 9 years, divided into three separate samples of 20. Two samples of 20 were used to examine the intrarater reliability of two different assessors, and the third sample of 20 was used to establish interrater reliability. Children’s TGMD-3 performances were video-recorded and later assessed using an intraclass correlation coefficient, a kappa statistic, and a percent agreement calculation. The intrarater reliability of the locomotor subtest, ball skills subtest, and gross motor total score ranged from 0.69 to 0.77, and percent agreement ranged from 87 to 91%. The interrater reliability of the locomotor subtest, ball skills subtest, and gross motor total score ranged from 0.56 to 0.64. Percent agreement of 83% was observed for locomotor skills, ball skills, and total skills, respectively. Hop, horizontal jump, and two-hand strike assessments showed the most difference between the assessors. These results show acceptable reliability for the TGMD-3 to analyze children’s gross motor skills.